Early and late human capital investments, borrowing constraints, and the family - Elizabeth M. Caucutt; Lance Lochner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2012)
This paper investigates the importance of family borrowing constraints in determining human capital investments in children at early and late ages. We begin by providing new evidence from the Children of the NLSY (CNLSY) which suggests that borrowing constraints bind for at least some families with young children. Next, we develop an intergenerational model of lifecycle human capital accumulation to study the role of early versus late investments in children when credit markets are imperfect. We analytically establish the importance of dynamic complementarity in investment for the qualitative nature of investment responses to income and policy changes. We extend the framework to incorporate dynasties and use data from the CNLSY to calibrate the model. Our benchmark steady state suggests that roughly half of young parents and 12% of old parents are borrowing constrained, while older children are unconstrained. We also identify strong complementarity between early and late investments, suggesting that policies targeted to one stage of development tend to have similar effects on investment in both stages. We use this calibrated model to study the effects of education subsidies, loans and transfers offered at different ages on early and late human capital investments and subsequent earnings in the short-run and long-run. A key lesson is that the interaction between dynamic complementarity and early borrowing constraints means that early interventions tend to be more successful than later interventions at improving human capital outcomes.
Keywords: 330; Bildungsinvestition; Lebenszyklus; Bildungsfinanzierung; Verschuldungsrestriktion; Familie; USA